Capacity for work and psychosocial mental health factors: a sample of portuguese health professionals - Ana Gomes; Pedro Bem-Haja; Afonso Alberty; Sonia Brito-Costa; Mª Isabel Ruiz Fernández; Carlos Silva; Hugo de Almeida (INFAD, 2015)
The ability to work proved to be a good predictor of work performance. This capacity has been affected by psychosocial factors at work, especially mental health. OBJECTIVE: To explore and identify the relationship between psychosocial factors of health and well-being at work and mild mental disturbance and sociodemographic factors, as well as to determine which psychosocial factors affect perceptions of ability to the work of workers in the health sector. Methods: The ICT and COPSOQ (medium version) questionnaires were applied to a sample of 150 professionals active in the health sector. Results: The results demonstrate that the sociodemographic variables gender and age are influenced by the psychosocial factors of health and that the capacity for work can be influenced by the sex and experienced burnout. Conclusion: Based on the result of this and the various studies carried out until then on the subject, there is a need for workplaces to focus on creating an environment conducive to the maintenance of workers' mental health and well-being.